Organocatalysis : stereoselective reactions and applications in organic synthesis - Benaglia, Maurizio; Benaglia, Maurizio (De Gruyter, 2021)
Organocatalysis is considered today one of the three pillars in asymmetric catalysis, along with biocatalysis and organometallic catalysis. The possibility to combine organocatalysis with radical chemistry, photocatalysis and enabling technologies opened new avenues in organic synthesis.